Development of computer learning and basic network e-modules - Marta, Satria Ami; Suparno, Suparno; Usmeldi, Usmeldi; Apriyus, Devri Ramdhan (Universitas Negeri Padang, 2020)
This research is motivated by the limitations of time learning that can be used by students in the class with the characteristics of vocational learning that requires students to know with skills (competencies). The teacher-centred learning process also slows the level of mastery of the material that students should have. The purpose of this research is to produce the appropriate e-modules used in the subjects of computer and basic network students in grade X TKJ at SMK. The type of this research was Research and Development by using ADDIE development model. This type of development research is with analysis (analysis) needs to be developed, design to choose Media, design and make media, development (development) test Practicality, practical done by 1 teacher and 30 students, implementation is done implementation in students by teacher, and Evaluation (evaluation) of data assessment result of multimedia-based learning module deserves to be used in Classroom as a simulation tool learning computer lessons and basic networks. Multimedia-based learning modules are applied because they are quality, easy to use and have a fascination if used in the learning process.